THEORETICAL ASPECTS OF DIGITAL CREATION TOPOGRAPHIC PLAN: Array - Afanasyev, O.; Zavada, I. (Municipal economy of cities (Technical science), 2021)
Theoretical bases of creation of the digital topographic plan of district are considered, the analysis of the materials used for creation of the digital topographic plan of district is carried out. Types and features of application of topographic plans are analyzed. The most suitable geo-basis for creating a digital plan has been identified. Studies have shown that a 1: 500 scale geo-base is quite informative and most optimal for creating digital and conventional topographic plans in the city. Without additional removal, 1: 500 scale plans allow for the transition to smaller scale plans. According to current national regulations, a single coordinate and altitude system should be used to create topographic plans. Today, the only state coordinate system USK-2000 is used, which replaced the coordinate system SK-42, which is based on the Krasovsky ellipsoid and the Gauss-Krueger projection. Possibilities of development of electronic topographic plans with use of modern software complexes are investigated. Computer software allows you to process data as accurately as possible and perform tasks quickly. Among the main software packages used to create an electronic topographic plan of the area are AutoCAD, Digitals, Geonics, COMPASS, MapInfo Pro, Topocad. The choice of software product depends on the breadth of the task, the modernity of surveying instruments and their own software. An analysis of the software used in the creation of digital maps and topographic plans, which showed that the choice of a particular product depends on the breadth of the task, the modernity of surveying instruments and their own software. AutoCAD software is universal and fully adapted to modern geodetic problems. The use of AutoCAD software will ensure the final processing of data obtained during field work and the completion of the digital topographic plan of the area. The procedure for creating a digital topographic plan of the area using Digitals and AutoCAD software is considered. Creating a digital topographic plan of the area is a complex process consisting of several stages, which are described in the article.